TAXONOMY BLOOM DALAM KETERAMPILAN BERBAHASA - ulil albab (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2021)
Language skills are one of the keys to success in the process of learning foreign languages, to see success in one language skill certainly requires evaluation. This study uses Benjamin S Bloom's theory which can be used to see the level of cognitive ability and the suitability of the evaluation process to the learning outcomes that have been conceptualized by lecturers in the semester learning plan. The purpose of this research is to analyze the quality of the Arabic language skills test questions, analyze the suitability of the Arabic language skills test questions to Bloom's taxonomic concepts, and analyze the suitability of the test questions to learning outcomes. By using purposive sampling techniques, this research includes quantitative research that departs from theory to the field to be tested for correctness. This research proves that the quality of Arabic exam questions in five expertise courses in the Arabic Language and Literature study program, Faculty of Adab and Humanities is still in a low stage. This can be seen from the taxonomic level that the concept of making questions by lecturers is still in the realm of C1 to C3 only, meaning that the evaluation process by lecturers has not reached the highest level.Then the Arabic exam question items have not fully followed the concept of Bloom's taxonomy, this can be proven on the question sheets given by lecturers on average on one exam question sheet only tests at the C1 level for example defining. The achievement of learning from three aspects, namely knowledge, attitudes and skills is also not fully visible in the problem, this indicates that learning evaluation tends to look at cognitive abilities only.